Optimizing Compressive Strength of Micro- and Nano-silica Concrete by Statistical Method - Mahsa Zarehparvar-Shoja; Hamid Eskandari-Naddaf (Salehan Institute of Higher Education, 2017)
In recent years, the use of nano-particles to improve the properties of concrete has created a new perspective on concrete technology. Studies in this field indicate improved concrete properties and higher strength by adding nano and micro silica particles to concrete mixes. In this regard, 12 mixing designs with different amounts of these admixtures with three types of cement strength classes (525,425,325) and 36 cubic samples (10 × 10 × 10) were designed and tested to measure compressive strength, of which we have only used 6 mixing plans in this research. The purpose of this research is to present a new method for concrete mix design by optimizing principles. Therefore, in this paper, the Taguchi statistical methods and the factorial design of the optimal mixing plan for this type of concrete are used to reduce the number of experiments to predict the optimal composition of the materials. The results obtained from the MINITAB software show that the effect of combined micro-silica and nano-silica on the compressive strength is in one direction and the effect of these two factors is more than cement strength grade of the cement and also the optimal value for micro-silica and nano-silica are estimated to have an optimum amount of micro-silica and nano-silica of 95 and 38 grams, respectively.